Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1152/ajprenal.00065.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ signaling and membrane potential in descending vasa recta pericytes and endothelia

Abstract: We devised a method for removal of pericytes from isolated descending vasa recta (DVR). After enzymatic digestion, aspiration of a descending vas rectum into a micropipette strips the pericytes from the abluminal surface. Pericytes and denuded endothelia can be recovered for separate study. Using fura 2-loaded preparations, we demonstrated that 10 nM angiotensin II (ANG II) elevates pericyte intracellular Ca(2+) concentration ([Ca(2+)](i)) and suppresses endothelial [Ca(2+)](i). The anion transport blocker pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 24 publications
7
70
0
Order By: Relevance
“…As expected, BK generates a peak-and-plateau Ca 2ϩ response, enhances NO generation (Fig. 8), and induces vasodilation (112,129,130). An unexpected finding is that the vasoconstrictor ANG II suppresses basal Ca 2ϩ and inhibits BK-, acetylcholine-, thapsigargin-, and cyclopiazonic acid-induced Ca 2ϩ responses in DVR endothelia (Fig.…”
Section: Role Of Dvr Endothelia In the Regulation Of Vasoactivitysupporting
confidence: 71%
See 4 more Smart Citations
“…As expected, BK generates a peak-and-plateau Ca 2ϩ response, enhances NO generation (Fig. 8), and induces vasodilation (112,129,130). An unexpected finding is that the vasoconstrictor ANG II suppresses basal Ca 2ϩ and inhibits BK-, acetylcholine-, thapsigargin-, and cyclopiazonic acid-induced Ca 2ϩ responses in DVR endothelia (Fig.…”
Section: Role Of Dvr Endothelia In the Regulation Of Vasoactivitysupporting
confidence: 71%
“…As expected for signaling via the ANG II AT 1 receptor, a classic peak-and-plateau intracellular Ca 2ϩ response is elicited in fura 2-loaded pericytes ( Fig. 3) (130,176). Both whole cell electrophysiological recording and measurements with a potentially sensitive fluorescent probe showed that ANG II depolarizes the pericyte cell membrane (Fig.…”
Section: Vasoactivity Of Dvrsupporting
confidence: 54%
See 3 more Smart Citations